Productivity change in commercial fisheries: An introduction to the special issue. (December 2015) - Walden, John; Fissel, Ben; Squires, Dale; Vestergaard, Niels
Abstract: Productivity is a key economic indicator that measures the relationship between inputs used to produce a product, and the amount of product produced. Productivity change measures how productivity has changed through time. In traditional land based industries, these two economic metrics have been extensively measured and studied. Until recently, this has not been true for commercial fishing fleets. This article provides an overview of productivity as an economic performance metric, and highlights specific studies of productivity change in commercial fisheries during the past 50 years. It concludes with an introduction to the articles contained in this special edition. Highlights: A survey of the theory and applications of productivity change in commercial fisheries is presented. Productivity is a key economic indicator of the relationship between input quantities and the amount of output produced. The two primary source of productivity gains are changes in efficiency and technological change. Unbiased measures of productivity change require adjusting for biomass change. Productivity change is most commonly measured using index numbers.